2011
DOI: 10.1111/j.1365-2788.2011.01511.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning Disability Liaison Nursing Services in south‐east Scotland: a mixed‐methods impact and outcome study

Abstract: The LDLN Services were valued by stakeholders by achieving person-centred outcomes. With their expert knowledge and skills, the liaison nurses had an important role in developing effective systems and processes within general hospital settings. The outcomes highlight the importance of supporting and promoting LDLN Services and the challenges in delivering the multifaceted elements of the role. There is a need to take account of the complex and multidimensional nature of the LDLN role and the possible tensions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 36 publications
(78 reference statements)
1
62
0
Order By: Relevance
“…Similar to the findings of Brown et al, 65 the LDLN role was found by this study to comprise three key elements: clinical patient care; education and practice development; and strategic organisational development. In addition, the LDLNs had a role as champion for the needs of people with learning disabilities that straddled all these elements.…”
Section: Elements Of the Learning Disability Liaison Nurse Rolesupporting
confidence: 76%
See 1 more Smart Citation
“…Similar to the findings of Brown et al, 65 the LDLN role was found by this study to comprise three key elements: clinical patient care; education and practice development; and strategic organisational development. In addition, the LDLNs had a role as champion for the needs of people with learning disabilities that straddled all these elements.…”
Section: Elements Of the Learning Disability Liaison Nurse Rolesupporting
confidence: 76%
“…5 A literature search found only one research study focusing on the effect of the LDLN in acute hospital settings. Brown et al 65,72 investigated the impact of LDLN services across four Scottish NHS boards. The authors found that the LDLN role was complex and had three key dimensions: clinical patient care, education and practice development, and strategic organisational development.…”
Section: Healthcare For Allmentioning
confidence: 99%
“…These barriers result in health needs remaining unmet and contribute to avoidable and preventable mortality (Alborz et al ; Heslop et al ; Emerson & Hatton ; Taggart & Cousins ). To promote and enable equality of access to universal health services, models of additional support, such as ID liaison nurses, have been recommended and may offer part of the solution in relation to diabetes management, education and care coordination (Brown et al ; Iacono et al ). Based within mainstream health services, the liaison nurses work with people with ID, their families and healthcare practitioners to provide additional support and expertise to help ensure that people with ID have equality of access and health outcomes (Backer et al ; Brown et al ).…”
Section: Discussionmentioning
confidence: 99%
“…However, although there is evidence to suggest that learning disability liaison nursing is valued by stakeholders, 197 and that promoting access and equity is an important part of the role, 198 there appears to have been little formal evaluation of the role 199 and its impact is unclear. Others suggested that the role of a dementia navigator could be non-clinical.…”
Section: Dementia Co-ordinators/support Workersmentioning
confidence: 99%